2014
DOI: 10.1002/pi.4733
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystals from star‐like clusto‐supramolecular macromolecules

Abstract: Clusto‐supramolecular liquid crystals (LCs) can be designed through attaching organic ligands onto the surface of inorganic nanoclusters, in which the ligands form the arms in star‐like supramolecular macromolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…[14] These nanosized polyanionic oxoclusters have been considered as ideal models for understanding the selfassembly process of liquid crystalline organic-inorganic hybrids because of their discrete structural character. [15] POMs are also emerging in areas related to energy conversion/storage and information technology owing to their remarkable electron reservoir properties. [16] The formation of POM-based mesomorphic materials has been mostly realized by ion exchange reactions with mesogenic cations, yielding surfactantencapsulated POMs.…”
Section: Introductionmentioning
confidence: 99%
“…[14] These nanosized polyanionic oxoclusters have been considered as ideal models for understanding the selfassembly process of liquid crystalline organic-inorganic hybrids because of their discrete structural character. [15] POMs are also emerging in areas related to energy conversion/storage and information technology owing to their remarkable electron reservoir properties. [16] The formation of POM-based mesomorphic materials has been mostly realized by ion exchange reactions with mesogenic cations, yielding surfactantencapsulated POMs.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] The polyanionic feature of PMs allows them to interact with many positively charged molecules, resulting in various nanostructures and functionalm aterials. [20][21][22] Among them,t he multivalent electrostatic interactions between PM clusters and cationic proteinso rp eptides are particularly attractive in terms of the exploration of potential bio-applications, such as selectively precipitatingp rion virus, [23] affecting the activity of enzymes, [24] inhibiting the 1D self-assembly of disease-relateda myloid polypeptides, [25] and controlling the hydrolytic cleavage of protein or peptide chains. [26] We have re-cently demonstrated that Keggin-types ilicotungstic acid( PM-3, see Figure 1a)c an drive the self-assembly of facial-like cationic peptide (L1, Figure 1b)i nto uniform nanofibers in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of research has been undertaken to control the shapes and sizes of supramolecular nanostructures with potential applications in fields such as materials science, molecular electronics and biomimetic chemistry . Rod–coil molecules have a strong tendency to self‐assemble into diverse supramolecular nanoscale structures .…”
Section: Introductionmentioning
confidence: 99%